Psychological strengths mediating the stress-coping experience : implications for mental health in school-going adolescents from low-income communities of the Cape Metropole - Harrison, Carmen (Stellenbosch : Stellenbosch University., 2020)
Thesis (PhD)--Stellenbosch University, 2020.